2004
DOI: 10.1111/j.1523-1755.2004.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of urinary pH with body weight in nephrolithiasis

Abstract: We conclude that urinary pH is inversely related to body weight among patients with stones. The results confirm the previously proposed scheme that obesity may sometimes cause uric acid nephrolithiasis by producing excessively acid urine due to insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
199
3
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 353 publications
(228 citation statements)
references
References 25 publications
12
199
3
7
Order By: Relevance
“…The inverse relationship reported by Maalouf et al (2004) for body weight and urinary pH remained stable when these authors adjusted 24h-UpH for the body's acid load using urinary sulfate, as a raw estimate of NAE. However, whether an NAE-adjusted 24-h urinary pH does actually correlate with adiposity can only be proved if biochemically analyzed NAE is used instead of excretion parameters as sulfate because a high protein intake and consequently high sulfate excretion does not automatically result in a high NAE (Sebastian et al, 2002;.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The inverse relationship reported by Maalouf et al (2004) for body weight and urinary pH remained stable when these authors adjusted 24h-UpH for the body's acid load using urinary sulfate, as a raw estimate of NAE. However, whether an NAE-adjusted 24-h urinary pH does actually correlate with adiposity can only be proved if biochemically analyzed NAE is used instead of excretion parameters as sulfate because a high protein intake and consequently high sulfate excretion does not automatically result in a high NAE (Sebastian et al, 2002;.…”
Section: Introductionmentioning
confidence: 92%
“…It can be quantified in 24-h urines by titration methods (Remer andManz, 1994, 1995a;Sebastian et al, 2002) and can be estimated by the potential renal acid load (PRAL), reflecting the dietary acidity (Remer and Manz, 1995b; and a body surface area (BSA)-dependent organic acid anion component (OA), reflecting primarily endogenous acids (Manz et al, 1984;Berkemeyer and Remer, 2006). Recently, Maalouf et al (2004) reported an inverse relationship between 24-h urinary pH (24h-UpH) and body weight, the latter taken as an indicator of obesity and peripheral insulin resistance, in patients with nephrolithiasis. Consequently, excess adipose tissue could contribute to lower urinary pHs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations